Molecular Characterization of Bombyx mori Cytoplasmic Polyhedrosis Virus Genome Segment 4 - Ikeda, Keiko (American Society for Microbiology, 2001)
The complete nucleotide sequence of the genome segment 4 (S4) of Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) was determined. The 3,259-nucleotide sequence contains a single long open reading frame which spans nucleotides 14 to 3187 and which is predicted to encode a protein with a molecular mass of about 130 kDa. Western blot analysis showed that S4 encodes BmCPV protein VP3, which is one of the outer components of the BmCPV virion. Sequence analysis of the deduced amino acid sequence of BmCPV VP3 revealed possible sequence homology with proteins from rice ragged stunt virus (RRSV) S2, Nilaparvata lugens reovirus S4, and Fiji disease fijivirus S4. This may suggest that plant reoviruses originated from insect viruses and that RRSV emerged more recently than other plant reoviruses. A chimeric protein consisting of BmCPV VP3 and green fluorescent protein (GFP) was constructed and expressed with BmCPV polyhedrin using a baculovirus expression vector. The VP3-GFP chimera was incorporated into BmCPV polyhedra and released under alkaline conditions. The results indicate that specific interactions occur between BmCPV polyhedrin and VP3 which might facilitate BmCPV virion occlusion into the polyhedra.